UCA?s North American Tunneling Conference Set For Los Angeles - Steve Kral (Society for Mining, Metallurgy & Exploration)
The Underground Construction Association?s (UCA) 2014 North American Tunneling (NAT) conference is expected to attract about 1,000 tunneling and underground construction professionals. With the theme ?Mission Possible,? attendees from around the world will hear the latest in tunneling and underground construction technology in the two-and-a-half days of technical sessions. The meeting is scheduled for June 24-27 at the JW Marriott Los Angeles Live in Los Angeles, CA. In addition to the technical programming, the accompanying exhibit has attracted 143 exhibitors in 162 booths. And the conference will offer short courses and plenty of social activities that will provide attendees the opportunity to catch up with each other. In addition, a proceedings volume containing all of the 128 papers will be available. An impressive lineup of sponsors will help attendees enjoy the conference. They include Brierley Associates, Kiewit Infrastructure Group, Parsons, Skanska, Traylor Bros., MWH and HNTB.